The visual character of colonial housing in Palembang Case study: Colonial housing settlement of Talang Semut in Palembang - Muhammad Fajri Romdhoni; Hendi Warlika Sedoputra (Institut Teknologi Sepuluh Nopember, 2017)
Palembang, having been one of the oldest city in Indonesia has inherited buildings that define an era. One of those remains are the traces of the colonial buildings in Palembang. The buildings that were built in those era are very predominant to it’s surrounding. The old Palembang area is divided with the 16 ilir in Palembang is an economic sector and the merdeka corridor is the government sector and also the Talang Semut area as a housing and settlement sector. This paper is about the traces of colonial building in the old colonial building in Palembang, represented with the Talang Semut area that have transformed into commercial places. The methods used in this study are using a visual research study to pinpoint the existing nature of the building and the transformation of the buildings as a result of changes in buildings function from settlements into micro commercial areas and also using space syntax analysis as a quantitative method to see how the streets have effected the transformation of the buildings. The transformation of Dutch and colonial places are found many in the colonial settlements in the city of Indonesia and have shaped the vibrant colors of cities in Indonesia. The Talang Semut area acts as one of the areas that transformed from settlements into micro economic, such as stores and culinary spots. The transformation of function have very much affected the visual expression of its original facade and therefore affected the character of the colonial housing settlements of Talang Semut in Palembang.